1996
DOI: 10.2337/diacare.19.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Deviation from Developmentally Appropriate Self-Care Autonomy: Association with diabetes outcomes

Abstract: The findings indicate caution about encouragement of maximal self-care autonomy among youth with IDDM and suggest that families who succeed in maintaining parental involvement in diabetes management may have better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
201
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(212 citation statements)
references
References 14 publications
9
201
0
2
Order By: Relevance
“…Conversely, patients from two-parent households have greater presumed family support, which may include a stay-at-home parent who is overly attentive to perceived changes and inclined to seek medical attention. The dynamics of a patient's household seemed to play a role in postoperative management in our study, which is consistent with existing literature examining home life, family support, and the quality of home care provided after a medical procedure [9,11,37,57]. These findings support the importance of preoperative assessment of social support and teaching pain management strategies to patients and caregivers (Table 8).…”
Section: Background and Rationalesupporting
confidence: 90%
See 1 more Smart Citation
“…Conversely, patients from two-parent households have greater presumed family support, which may include a stay-at-home parent who is overly attentive to perceived changes and inclined to seek medical attention. The dynamics of a patient's household seemed to play a role in postoperative management in our study, which is consistent with existing literature examining home life, family support, and the quality of home care provided after a medical procedure [9,11,37,57]. These findings support the importance of preoperative assessment of social support and teaching pain management strategies to patients and caregivers (Table 8).…”
Section: Background and Rationalesupporting
confidence: 90%
“…Older patients also spent longer time in the apparatus and required a greater number of antibiotics. Many factors could have accounted for these findings, including medical indication for external fixation, goal(s) of treatment, knowledge of and adherence to postoperative care, and developmental stage as it impacts physical growth, cooperation, and postoperative self-care [33,41,57]. Appropriate education regarding these findings will establish reasonable expectations of treatment duration and potential challenges.…”
Section: Background and Rationalementioning
confidence: 99%
“…The increasing independence of adolescents from their parents in carrying out diabetes tasks (8,10) may make monitoring by both mothers and fathers especially important (11). Ellis et al (9) found that diabetes-specific monitoring during adolescence was associated with better metabolic control via its association with better regimen adherence.…”
mentioning
confidence: 99%
“…Parental monitoring involves regular contact with adolescents regarding their daily activities and involves knowledge about and supervision of those activities (6). Although the diabetes literature has examined constructs related to parental monitoring (e.g., involvement) that are associated with positive diabetes outcomes (7,8), involvement (i.e., who is responsible for diabetes tasks) is not synonymous with monitoring (i.e., parent really knows that diabetes tasks are completed). For instance, an adolescent could manage diabetes care tasks independently (low parental involvement), while the parent monitors the success of those independent efforts (high parental monitoring).…”
mentioning
confidence: 99%
“…13,27 In addition, there is growing consensus that youth whose parents are more engaged in diabetes management are more adherent than youth whose parents are less involved in diabetes tasks. 13,28 These associations, however, have not previously been assessed in patients initiating CGM. In this study, we found lower diabetes-specific family conflict reported by patients and parents interested in starting CGM in comparison with a general population of youth with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 90%